STRATEGI PENDIDIKAN ABAD 21 DALAM PENINGKATKAN EFEKTIFITAS PEMBELAJARAN - Rodifatul Chasanah; Ali Mustofa; Zusril Bayu Putra Mahendra; Maulana Syarif Afwa (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The development of digital technology demands effective and adaptive learning, especially in post-pandemic blended learning conditions. In 2021, teachers faced the challenge of limited face-to-face learning, where some students studied at school and others studied from home. Observations at SD Negeri Diwek 1 showed that Islamic Religious Education (PAI) learning was still dominated by lectures and literacy with minimal use of technology, resulting in students tending to be passive and less enthusiastic. This study aims to describe the application of 21st-century education strategies in improving the effectiveness of PAI learning through the integration of information technology and to identify the obstacles and solutions faced by teachers. This study used a descriptive qualitative method with observation, interview, and documentation techniques. The results showed that the application of flipped learning with digital media and learning videos was able to increase student independence and engagement. The obstacles found included limitations in devices, internet networks, and technological capabilities. Teachers overcame these obstacles by adjusting methods and providing simple technology training.